The road to Bloody Sunday : Father Gapon and the St. Petersburg Massacre of 1905 - Sablinsky, Walter (Princeton : Princeton University Press, 1976)
Bibliotheek François Vercammen
Met aantekeningen door François Vercammen
Engels
Monografie